Outcome following cervicothoracic junction fusion in T1 pathological fracture of breast cancer spinal metastases: a case report - Astawa, Ni Made Puspa Dewi; Wiguna, I. Gusti Lanang Ngurah Agung Artha; Purvance, Ivander; Stanu, Gusti Ngurah Putra; Simanjuntak, Herryanto Agustriadi; Putra, I. Gede Mahardika (International Journal of Research in Medical Sciences, 2020)
The cervicothoracic junction (CTJ) is defined as the area extending from vertebral segment C7 to T2. Spinal metastases of CTJ are rare, range from 10% to less than 20%. A 47-year-old woman complained sensory and motor disturbance since 3 weeks prior to admission. History of lump on the left breast was confirmed. Neurological deficit was confirmed as ASIA C at the time of diagnosis. MRI finding suggest fracture of T1 vertebral body with kypothic angle 28° that causing anterior compression of spinal cord. The patient underwent decompression and posterior fusion from C4 to T4. A biopsy sample was also collected from the spine and left breast to confirm the diagnosis. Patient evaluation was done during discharge and at certain points of follow-up for improvement on its neurological, pain, and functional status. An MRI evaluation was performed to evaluate spinal stability and fusion. Significant improvements were observed in patient ambulatory and pain status. Cervicothoracic junction fusion procedure is a considerable choice for the management of pathological vertebral fractures with cervicothoracic junction involvement caused by spinal metastases of breast cancer.